Efektivitas pelaksanaan sertifikasi halal pada warung makan di Desa Wirogunan, Kartasura, Sukoharjo - Muhammad Soffin Arfianto; M. Usman (Journal of Halal Industry Studies, 2026)
Wirogunan Village is an area with significant culinary activity; consequently, the availability of halal-certified eateries is crucial to protecting Muslim consumers. This study examines the effectiveness of halal certification implementation in food stalls in Wirogunan Village, Kartasura District, Sukoharjo Regency, in accordance with Law Number 33 of 2014 concerning Halal Product Assurance, which requires all food and beverage products to have halal certification to protect Muslim consumers. This research was field-based and employed an empirical legal approach. Data were obtained through interviews with food stall business owners and related parties, as well as documentation studies from various legal and policy literature. Data analysis was conducted using the interactive model of Miles and Huberman. The results of the study indicate that the implementation of halal certification in food stalls in Wirogunan Village has not been running effectively. This condition is caused by business owners' limited understanding and awareness of the importance of halal certification, a lack of socialization from related parties, limited facilities and infrastructure supporting the certification process, and the perception that the certification process is complicated and costly. In addition, cultural factors that are not accustomed to paying attention to or asking about the halal status of food stalls also contribute to low business compliance. Thus, implementing the halal certification policy still requires strengthening socialization and mentoring, and increasing awareness among both business actors and consumers, so that the goal of protecting Muslim consumers can be optimally achieved.